Conceptualization of Community Wellness in Three First Nations Communities - McBeath, Brittany (2020)
Introduction: It is well known, and well documented that Indigenous conceptualizations of wellness differ from Western conceptualizations. Using Western parameters and formulations to appraise Indigenous health and wellness is highly problematic. Purpose: To address the need for Indigenous community-led conceptualizations of wellness in order to inform the creation of more culturally relevant and applicable indicators of Indigenous community wellness. Methods: Conceptualizations of wellness were explored in three First Nations communities participating in the Kahnawà:ke Schools Diabetes Prevention Project (KSDPP) Community Mobilization Training (CMT). Kane & Trochim’s (2007) Concept Mapping for Planning and Evaluation was used to systematically collect and analyze data in partnership with each Indigenous community. The research consisted of three phases including Wellness Indicator Talking Circles, online unstructured sorting and rating, and concept map interpretation sessions. Data Analysis: Using Concept Systems® Global Max™ software, three data analysis steps were conducted to create the concept maps including a similarity matrix, multidimensional scaling, and hierarchical cluster analysis. All interpretations of these outputs were completed using a participatory approach. Results: The themes of balance and wholism, intergenerational relationships, the importance of Indigenous language and culture, connectedness, food systems and the environment were prominent in all three communities. However, each community’s concept map was distinct, highlighting that the meaning of wellness within each community was directly related to their local history, context, ideals, and resources. Discussion: Given the diversity of perspectives, histories, cultures, contexts, values, and experiences across Indigenous nations, establishing generalizable Indigenous community wellness indicators is unrealistic. Conceptualizing Indigenous community wellness is a process that should be locally determined to foster ownership and ...